Model Hubungan Antara Penyertaan, Komitmen Akademik dan Perkembangan Psikososial Pelajar Universiti - Fauziah, Md Jaafar (2013)
Higher education institutions are facing challenges in producing quality graduates who are not only academically sound, but also holistically well-developed, and ready to enter the job market immediately upon graduation. Therefore, studies focusing on the factors which might influence student psychosocial development processes in the context of the local university are highly relevant. Previous studies show inconsistent findings with regard to the contribution of student involvement towards their psychosocial development. Furthermore, past researchers had only examined the dimensions of psychosocial development in separate studies, rather than holistically in a single study. In this study, two prevalently used theories in the psychosocial field, namely Involvement Theory and Psychosocial Development Theory, were combined to form a mediation model to better explicate the relationship between student involvement and psychosocial development. The model mapped the contribution of each dimension of student involvement on academic commitment, and in turn, its impact on student psychosocial development. Using the survey research method, the study involved 347 undergraduates who gave feedback to a total of 86 items in the study questionnaire. Data analysis involved descriptive and inferential statistics, and model testing. Holistic evaluation of the model found that the proposed structural model fit the data. The findings showed that student involvement with peers influenced student psychosocial development both directly and indirectly; student involvement with the community influenced student psychosocial development directly; and student involvement with the academic staff significantly influenced students’ psychosocial development indirectly, i.e., through their commitment in academic-related activities. The study has provided empirical support for the combination of Involvement Theory and Psychosocial Development Theory in explaining how student involvement with other individuals could contribute towards enhancing the students’ psychosocial development. In practical terms, there should, in light of the findings, be more avenues provided for university students to carry out engaging activities on campus with their peers and the academic staff, as well as beyond the campus with the wider community.